Assessing Foreign Aid’s Influence on Tourism Demand for Developing Economies: When More Isn’t Better - Karim Barkat (17823665) (2025)
The existing literature has largely overlooked the effects of foreign aid on tourism demand in developing countries, and the channels through which this relationship operates. This study fills this gap by examining the direct and indirect effects of aid on tourism demand using data from 96 developing countries spanning the period 1995 to 2020. We reveal the existence of an inverted U-shaped relationship where aid negatively affects tourism demand beyond a specific threshold. Our findings also suggest that institutional quality and political stability are crucial for maximizing the impact of aid, while human development and economic growth serve as key mediating channels. These results imply that to boost tourism demand, recipient countries should prioritize strengthening governance and institutional frameworks, while donors should target aid toward human development and infrastructure projects supporting the tourism sector. Focusing on these areas can help both donors and recipients reduce poverty and enhance economic resilience. Other Information Published in: Journal of Travel Research License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1177/00472875251349236